Pasteurella multocida: Molecular Biology, Toxins and Infection - Aktories, Klaus; Orth, Joachim Hans Christian; Adler, Ben (Springer, 2012)
This volume brings together contributions from experts in the field of Pasteurella research. Its covers areas such as comparative genomics, pathogenic mechanisms, bacterial proteomics, as well as a detailed description and analysis of PMT and its interaction with host tissues, cells, immune system, and signalling pathways.
Description based upon print version of record
Keywords: Aufsatzsammlung; Pathogenität; Pasteurella multocida